2020
DOI: 10.1002/advs.202003097
|View full text |Cite
|
Sign up to set email alerts
|

Deep Learning Enables Superior Photoacoustic Imaging at Ultralow Laser Dosages

Abstract: Optical‐resolution photoacoustic microscopy (OR‐PAM) is an excellent modality for in vivo biomedical imaging as it noninvasively provides high‐resolution morphologic and functional information without the need for exogenous contrast agents. However, the high excitation laser dosage, limited imaging speed, and imperfect image quality still hinder the use of OR‐PAM in clinical applications. The laser dosage, imaging speed, and image quality are mutually restrained by each other, and thus far, no methods have bee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
27
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 47 publications
(28 citation statements)
references
References 42 publications
0
27
0
Order By: Relevance
“…In our GANs, generators are designed based on U-net (Fig. 1c ), which has recently proven effective for multiscale image learning, especially PA image reconstruction 29 , 31 , 38 , 41 . The generator for 3D OR-PAM images contains 17 3D convolutional layers and roughly 43 million trainable parameters (Table S1 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In our GANs, generators are designed based on U-net (Fig. 1c ), which has recently proven effective for multiscale image learning, especially PA image reconstruction 29 , 31 , 38 , 41 . The generator for 3D OR-PAM images contains 17 3D convolutional layers and roughly 43 million trainable parameters (Table S1 ).…”
Section: Resultsmentioning
confidence: 99%
“…Computational strategies based on a deep neural network (DNN) have proved effective in improving such biomedical imaging modalities as optical microscopy, US imaging, magnetic resonance angiography (MRI), and computed tomography (CT) 29 37 . An especially interesting emerging application minimizes data acquisition times by reconstructing dense data from spatially or temporally undersampled sparse data 30 , 31 .…”
Section: Introductionmentioning
confidence: 99%
“…For more reliable results, it is necessary to develop better laser sources with faster repetition rates, less fluctuation, and more wavelengths. Motion correction can be applied to mitigate the inevitable motions [ 68 , 69 ], and vascular enhancement can be adopted to achieve high-quality blood vessel images [ 70 , 71 ]. From the improvement, if real-time 3D imaging is available, the heartbeat and vascular density could be more accurate.…”
Section: Discussionmentioning
confidence: 99%
“…In that work, a CNN architecture was developed mainly to improve out-of-focus lateral resolution of AR-PAM images, while background noise reduction was also observed. Zhao et al demonstrated good de-noising performance for OR-PAM images [28], yet the use of two wavelengths for PA excitation was required, which results in higher cost and more complexity of the imaging system (e.g., an optical parametric oscillator laser was used. ).…”
Section: Introductionmentioning
confidence: 99%